Fumaric Acid Esters Do Not Reduce Inflammatory NF-κB/p65 Nuclear Translocation, ICAM-1 Expression and T-Cell Adhesiveness of Human Brain Microvascular Endothelial Cells - Haarmann, Axel (Int J Mol Sci, 2015)
Dimethyl fumarate (DMF) is approved for disease-modifying treatment of patients with relapsing-remitting multiple sclerosis. Animal experiments suggested that part of its therapeutic effect is due to a reduction of T-cell infiltration of the central nervous system (CNS) by uncertain mechanisms. Here we evaluated whether DMF and its primary metabolite monomethyl fumarate (MMF) modulate pro-inflammatory intracellular signaling and T-cell adhesiveness of nonimmortalized single donor human brain microvascular endothelial cells at low passages. Neither DMF nor MMF at concentrations of 10 or 50 µM blocked the IL-1β-induced nuclear translocation of NF-κB/p65, whereas the higher concentration of DMF inhibited the nuclear entry of p65 in human umbilical vein endothelium cultured in parallel. DMF and MMF also did not alter the IL-1β-stimulated activation of p38 MAPK in brain endothelium. Furthermore, neither DMF nor MMF reduced the basal or IL-1β-inducible expression of ICAM-1. In accordance, both fumaric acid esters did not reduce the adhesion of activated Jurkat T cells to brain endothelium under basal or inflammatory conditions. Therefore, brain endothelial cells probably do not directly mediate a potential blocking effect of fumaric acid esters on the inflammatory infiltration of the CNS by T cells.